New species of Ribesaptera Heiss from eastern Madagascar (Hemiptera: Heteroptera: Aradidae) - Baňař, Petr; Heiss, Ernst; Hubáčková, Lenka (Zootaxa, 2016)
The rich flat bug fauna of Madagascar comprises eleven apterous genera of Mezirinae with 21 species (Heiss 2012, Heiss & Marchal 2012) to date, and all of them are endemic: Ambohitantelya Heiss & Baňař 2013 (1 sp.); Antsirabenus Heiss 2008 (2 spp.); Cervinotaptera Heiss & Marchal 2012 (1 sp.); Chlonocoris Usinger & Matsuda 1959 (3 spp.); Cimicomanes Kiritshenko 1959 (5 spp.); Classeyana Hoberlandt 1963 (1 sp.); Paulianum Hoberlandt 1957 (1 sp.); Pericartaptera Heiss 2009 (2 spp.); Ribesaptera Heiss 2011 (1 sp.); Robertiessa Hoberlandt 1963 (1 sp.) and Tananarivea Drake 1957 (3 spp.).